Impact of economic policy uncertainty on cash holdings: firm-level evidence from an emerging market. Issue 2 (4th March 2022) - Feng, Xunan; Lo, Y. Ling; Chan, Kam C.
ABSTRACT: We examine how economic policy uncertainty (EPU) affects firms' cash holdings and how such changes in cash holdings affect firm value and capital investment in China. Our findings suggest that firms that increase their cash holdings during high EPU have higher firm values and are less negatively impacted by the underinvestment problem. When a firm is non-state-owned, financially constrained, or is located in a province with low marketization, the impact of EPU on cash holdings is amplified. Furthermore, state-owned enterprises (SOEs) are less likely to increase cash holdings during elevated EPU, and consequently tend to have lower firm values.